India's multilateral foreign policy strategy: phases of its evolution. Issue 3 (4th May 2022) - Kumar, Rajan
ABSTRACT: Multilateralism in India's foreign policy underwent three distinct phases. A high decibel universalism rooted in morality and idealism marked the first phase (1947-1961). In the second phase (1961-1991), a gradual shift in strategy occurred. In terms of international relations, a phase of 'regime shifting' or 'parallel institutionalisation' began. The Non-Aligned Movement (NAM, 1961) and G-77 (1964) were constituted. The third phase of India's multilateralism began with the end of the Cold War in 1991. India embraced all sorts of organisations ranging from the G20 and QUAD to BRICS and the SCO. A period of 'multi-alignment' started.